Moisture-curable urethane hot-melt resin composition, laminate, and synthetic artificial leather

By optimizing the composition of polyols and polyisocyanates, the initial adhesion and heat resistance of the moisture-cured urethane hot melt resin are improved, and the shortcomings of the resin in the prior art are solved in terms of high temperature and alcohol resistance, so as to achieve the realization of the following requirements. A wider range of synthetic leather applications.

CN119137178AActive Publication Date: 2024-12-13DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD

Patent Information

Application Number
CN202380037596.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-02
Filing Date
2023-04-06
Publication Date
2024-12-13
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

The existing moisture-curing urethane hot melt resin compositions have shortcomings in initial adhesion, heat resistance, softness, hydrolysis resistance and wear resistance, especially in high temperature processing and alcohol resistance. The poor performance limits its use in applications such as synthetic artificial leather.

Method used

Reactants of polyol components and polyisocyanate components, including polymers and low molecular weight polyols, are adopted to form a crosslinked structure by reacting isocyanate groups with water, optimize the composition of carbamate prepolymers, and improve the bonding of resin compositions. and heat resistance, and enhance the softness and wear resistance of the resin by adjusting the ratio and type of polyol and polyisocyanate.

Benefits of technology

It has achieved a significant improvement in the initial adhesion, heat resistance, softness, hydrolysis resistance and wear resistance of the moisture-cured urethane hot melt resin composition, and is suitable for high-temperature processing and washing resistance applications. It has expanded its application scope in the fields of synthetic artificial leather and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137178A_ABST
    Figure CN119137178A_ABST
Patent Text Reader

Abstract

Provided is a moisture-curable urethane hot-melt resin composition capable of forming a cured product layer having excellent initial adhesiveness, heat resistance, hydrolysis resistance, alcohol resistance, and wear resistance. The moisture-curable urethane hot-melt resin composition contains a urethane prepolymer having an isocyanate group, which is a reactant of a polyol component and a polyisocyanate component. The polyol component contains a high-molecular-weight polyol component and a low-molecular-weight polyol component. The polymer polyol component contains: at least one polyol (A) selected from the group consisting of SA-based polyester polyols (A1), 1, 4-BD / AA-based polyester polyols (A2) having a number average molecular weight (Mn) of 8,000 or more, and 1, 6-HD / AA-based polyester polyols (A3) having a number average molecular weight (Mn) of 6,000 or more; and at least one polyol (B) selected from the group consisting of a polyester polyol (B1) other than the polyol (A) and a polyether polyol (B2). The low-molecular-weight polyol component contains a trifunctional polyol (D) having three hydroxyl groups per molecule and having a molecular weight of 300 or less. The ratio of the polyol (A) to the trifunctional polyol (D) satisfies the following formula: trifunctional polyol (D) (mmol) / polyol (A) (g) = 0.14-55 mmol / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a moisture-curable urethane hot-melt resin composition, a laminate, and a synthetic artificial leather. Background Art

[0002] Moisture-curable urethane hot-melt resin composition is a composition that is solid at room temperature and can be prepared without a solvent, and is a resin composition that is cured by moisture after heating and melting coating. Therefore, moisture-curable urethane hot-melt resin composition is widely used as various environmentally friendly adhesives because it does not use a solvent. This moisture-curable urethane hot-melt resin composition contains a urethane prepolymer, and the urethane prepolymer has a functional group such as an isocyanate group (NCO group) in the molecule, and the functional group can react with water (moisture) present in the air or in the coated substrate to form a cross-linked structure.

[0003] When used as various adhesives, moisture-curable urethane hot-melt resin compositions exhibit adhesive strength by moisture curing, and therefore it is difficult to exhibit excellent initial strength, and therefore a technology for exhibiting excellent initial adhesiveness has been proposed. For example, Patent Document 1 discloses a reactive hot-melt adhesive comprising: a "urethane prepolymer (1)" derived from an organic polyisocyanate compound (a) and a specified polyol (b1) and having an NCO group; and a "low molecular weight xylene resin (d1)" having no active hydrogen and having tackifying properties.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 5-065471 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The urethane prepolymer used for the moisture-curing urethane resin composition can also be used as an adhesive in the manufacture of artificial leather, synthetic leather and other synthetic leather. Synthetic leather is used as a material for the manufacture of various products such as shoes, clothing, handbags, furniture, and vehicle interior materials (such as dashboards, doors, consoles, seats). In the past, synthetic leather was usually a laminated body in which an epidermis layer, an adhesive layer (cured layer), and a substrate layer were stacked in sequence, and the cured layer was formed by various urethane prepolymers. For the cured layer constituting the synthetic leather used in the above-mentioned various products, it is required not only to have good softness, but also to have heat resistance that can withstand the heat during manufacturing and processing.

[0009] The reactive hot melt adhesive disclosed in the above-mentioned Patent Document 1 can achieve a certain effect in terms of the initial bonding force after curing when cured under a specified humidity environment. However, such conventional moisture-curable urethane hot melt resin compositions have a low thermal softening point after curing and a less mesh structure after curing than two-component curable polyurethane resin compositions, so they are limited in their application to applications that require heat resistance and processing at high temperatures, such as the above-mentioned synthetic leather. In addition, when conventional moisture-curable urethane hot melt resin compositions are used for clothing purposes, in addition to insufficient hydrolysis resistance to the extent that they can withstand washing, they also have insufficient abrasion resistance, and may peel off from the substrate due to friction such as rubbing. In addition, the current coronavirus pandemic also requires resistance to alcohol disinfection.

[0010] To this end, the present invention aims to provide a moisture-curable urethane hot-melt resin composition capable of forming a cured layer having excellent initial adhesion, heat resistance, flexibility, hydrolysis resistance, alcohol resistance and abrasion resistance.

[0011] Solutions for solving problems

[0012] The present invention provides a moisture-curable urethane hot-melt resin composition, which contains a reaction product of a polyol component and a polyisocyanate component, that is, a urethane prepolymer having an isocyanate group, wherein the polyol component contains a high-molecular-weight polyol component and a low-molecular-weight polyol component, and the high-molecular-weight polyol component contains: a polyester polyol (A1) having a structural unit derived from sebacic acid, a polyester polyol (A2) having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid and having a number average molecular weight of 8,000 or more, and a polyester polyol (A3) having a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid. At least one polyol (A) selected from the group consisting of polyester polyols (A3) having a unit number average molecular weight of 6,000 or more; and at least one polyol (B) selected from the group consisting of polyester polyols (B1) other than the polyol (A) and polyether polyols (B2), wherein the low molecular weight polyol component comprises a trifunctional polyol (D) having a molecular weight of 300 or less and having three hydroxyl groups in one molecule, and the ratio of the polyol (A) to the trifunctional polyol (D) satisfies the following: the trifunctional polyol (D) (mmol) / the polyol (A) (g) = 0.14 to 55 mmol / g.

[0013] Effects of the Invention

[0014] According to the present invention, there can be provided a moisture-curable urethane hot-melt resin composition capable of forming a cured product layer having excellent initial adhesion, heat resistance, flexibility, hydrolysis resistance, alcohol resistance and abrasion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic explanatory diagram for explaining the form of a sample used for evaluation in Examples.

[0016] Figure 2 This is an explanatory diagram for explaining the configuration of a gear oven used for evaluation of Examples. DETAILED DESCRIPTION

[0017] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.

[0018] <Moisture-curable urethane hot-melt resin composition>

[0019] The moisture-curable urethane hot-melt resin composition (hereinafter sometimes referred to as "resin composition") of one embodiment of the present invention contains a reactant of a polyol component and a polyisocyanate component, namely, a urethane prepolymer. The urethane prepolymer has an isocyanate group. Through the isocyanate group, the urethane prepolymer can react with water (moisture) present in the air or in a substrate coated with the resin composition to form a cross-linked structure, so the resin composition with the urethane prepolymer as the main component has moisture curing properties.

[0020] The polyol component used for the urethane prepolymer includes a high molecular weight polyol component and a low molecular weight polyol component. The high molecular weight polyol component includes the following polyols (A) and polyols (B). Polyol (A) is at least one selected from the group consisting of a polyester polyol (A1) having a structural unit derived from sebacic acid, a polyester polyol (A2) having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid and a number average molecular weight of 8,000 or more, and a polyester polyol (A3) having a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid and a number average molecular weight of 6,000 or more. Polyol (B) is at least one selected from the group consisting of a polyester polyol (B1) other than the above-mentioned polyol (A), and a polyether polyol (B2). In addition, the low molecular weight polyol component includes a trifunctional polyol (D) having a molecular weight of 300 or less and having three hydroxyl groups in one molecule. Furthermore, in the resin composition, the ratio of the polyol (A) to the trifunctional polyol (D) satisfies the following: trifunctional polyol (D) (mmol) / polyol (A) (g) = 0.14 to 55 mmol / g.

[0021] According to the above-mentioned constitution, the moisture-curable urethane hot-melt resin composition of the present embodiment can form a cured product layer having good initial adhesion, heat resistance, flexibility, hydrolysis resistance, alcohol resistance, and wear resistance. In addition, in one embodiment, the resin composition has good stability over time in a molten state. In addition, in one embodiment, the resin composition can contribute to providing a synthetic artificial leather having good cold resistance, bendability, hydrolysis resistance, flexibility, wear resistance, and heat resistance.

[0022] From the perspective of easily obtaining the above-mentioned effects, the preferred structure of the resin composition of the present embodiment will be described in detail below. It should be noted that, in the description of the following compounds (each polyol component and polyisocyanate component, etc.), unless otherwise specified, any one or more than two compounds in the specification can be used.

[0023] [Urethane prepolymer]

[0024] The urethane prepolymer is a reaction product of a polyol component and a polyisocyanate component and has an isocyanate group. The urethane prepolymer is preferably obtained by a polyaddition reaction of a polyol component and a polyisocyanate component, more preferably obtained by a polyaddition reaction of a polyol component and an excess of a polyisocyanate component and has an isocyanate group at the end.

[0025] The equivalent ratio (molar ratio; NCO group / OH group) of the isocyanate group (NCO group) of the polyisocyanate component constituting the urethane prepolymer to the hydroxyl group (OH group) of the polyol component is preferably 1.1 to 2.2, more preferably 1.4 to 2.0, and further preferably 1.5 to 1.9. By setting the NCO group / OH group within the above range, the processability at high temperature such as when used for clothing applications is improved, and a synthetic artificial leather with a better hand feel can be produced.

[0026] From the perspective of making the resin composition exhibit moisture curing properties, the urethane prepolymer is preferably the main component of the resin composition. Based on the mass of the solid content of the resin composition, the content of the urethane prepolymer can be 100% by mass, preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 90% by mass or more.

[0027] 〔Polyol ingredient〕

[0028] The polyol component used for the urethane prepolymer includes a high molecular weight polyol component and a low molecular weight polyol component. The high molecular weight polyol component is a group of polyols having a higher molecular weight than the low molecular weight polyol component, and a polymer is preferably used. The low molecular weight polyol component is a group of polyols having a lower molecular weight than the high molecular weight polyol component.

[0029] (Polyol component)

[0030] The high molecular weight polyol component used for the urethane prepolymer includes the polyol (A) described below and the polyol (B) other than the polyol (A). Among the polyol components, the high molecular weight polyol component is preferably the main component of the polyol component, and is preferably used in an amount larger than the low molecular weight polyol component. Based on the total amount of the polyol component, the proportion of the high molecular weight polyol component in the polyol component is preferably 60 to 99.8% by mass, more preferably 80 to 99.5% by mass, and further preferably 90 to 99% by mass.

[0031] (Polyol (A))

[0032] The polyol (A) is at least one selected from the group consisting of the following polyester polyols (A1) to (A3).

[0033] (A1): Polyester polyol (A1) having a structural unit derived from sebacic acid

[0034] (A2): A polyester polyol (A2) having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid and having a number average molecular weight of 8,000 or more

[0035] (A3): A polyester polyol (A3) having a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid and having a number average molecular weight of 6,000 or more

[0036] The polyester polyols (A1) to (A3) are crystalline polyols that can be solid at 60°C. By using the polyol (A), the resin composition can form a cured layer having good initial adhesion and flexibility, and it is easy to obtain a synthetic artificial leather having further good cold-resistant bending, flexibility and heat resistance. From these viewpoints, it is preferred to use at least the polyester polyol (A1) in the polyol (A).

[0037] Polyester polyol (A1) has a structural unit derived from sebacic acid (SA). Hereinafter, polyester polyol having a structural unit derived from sebacic acid is sometimes referred to as "SA-based polyester polyol". SA-based polyester polyol (A1) is a reactant of sebacic acid and diols, and is a bifunctional (hydroxyl number 2) polyol (diol). Preferably, SA-based polyester polyol (A1) is obtained by polycondensation of sebacic acid and diols.

[0038] As diols used for SA polyester polyol (A1), for example, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, hexanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 1,9-nonanediol and neopentyl glycol can be listed. Among them, 1,6-hexanediol is preferred. That is, polyester polyol (A1) is preferably a polyester polyol having a structural unit derived from sebacic acid and a structural unit derived from 1,6-hexanediol (hereinafter sometimes referred to as "1,6-HD / SA polyester polyol").

[0039] The number average molecular weight (Mn) of the SA polyester polyol (A1) is preferably 2,000 or more, more preferably 3,000 or more, further preferably 5,000 or more, and preferably 20,000 or less. The "number average molecular weight (Mn)" in this specification is a value converted to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, dimethylformamide (DMF) is used as the mobile phase and measured by GPC analysis under the following conditions (the same applies to the following examples).

[0040] · Measurement device: High-speed GPC device (trade name "HLC-8220GPC", manufactured by Tosoh Corporation)

[0041] Chromatographic column: TSK gel Super HM-N × 2,

[0042] TSK guardcolumn Super HH×1 piece

[0043] Detector: RI (differential refractometer)

[0044] Column temperature: 40℃

[0045] Flow rate: 0.5mL / min

[0046] Injection volume: 50μL

[0047] The polyester polyol (A2) has a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid. Hereinafter, the polyester polyol having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid is sometimes referred to as "1,4-BD / AA polyester polyol". The 1,4-BD / AA polyester polyol (A2) is a reaction product of 1,4-butanediol and adipic acid, and is a bifunctional (hydroxyl number 2) polyol (diol). Preferably, the polyester polyol (A2) is obtained by polycondensation of 1,4-butanediol and adipic acid.

[0048] The number average molecular weight (Mn) of the 1,4-BD / AA polyester polyol (A2) is 8,000 or more. By using the 1,4-BD / AA polyester polyol (A2) having an Mn of 8,000 or more, the resin composition can form a cured layer with good initial adhesion, and it is easy to obtain a synthetic artificial leather with better cold-resistant bending and softness. The Mn of the 1,4-BD / AA polyester polyol (A2) is preferably 20,000 or less.

[0049] The polyester polyol (A3) has a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid. Hereinafter, the polyester polyol having a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid is sometimes referred to as "1,6-HD / AA polyester polyol". The 1,6-HD / AA polyester polyol (A3) is a reaction product of 1,6-hexanediol and adipic acid, and is a bifunctional (hydroxyl number 2) polyol (diol). Preferably, the polyester polyol (A3) is obtained by polycondensation of 1,6-hexanediol and adipic acid.

[0050] The number average molecular weight (Mn) of the 1,6-HD / AA polyester polyol (A3) is 6,000 or more. By using the 1,6-HD / AA polyester polyol (A3) having an Mn of 6,000 or more, the resin composition can form a cured layer with good initial adhesion, and it is easy to obtain a synthetic artificial leather with better cold-resistant bending properties and softness. The Mn of the 1,6-HD / AA polyester polyol (A3) is preferably 20,000 or less.

[0051] From the perspective that the above-mentioned effect of the polyol (A) can be easily expressed in a good balance with the effects of other polyols described later, the proportion of the polyol (A) in the polymer polyol component is preferably 0.5 to 30 mass %, more preferably 1 to 20 mass %, and even more preferably 2 to 15 mass %, based on the total amount of the polymer polyol component.

[0052] (Polyol (B))

[0053] The polyol (B) is at least one selected from the group consisting of polyester polyols (B1) other than the above-mentioned polyol (A) and polyether polyols (B2).

[0054] The polyester polyol (B1) and the polyether polyol (B2) other than the polyol (A) are polyols having lower crystallinity than the polyol (A) and can be in a liquid state at 60° C. By using at least one of the polyester polyol (B1) and the polyether polyol (B2), the resin composition can form a cured layer having good flexibility, and it is easy to obtain a synthetic artificial leather having good cold resistance, flexibility, etc.

[0055] The polyester polyol (B1) is a polyester polyol other than the above-mentioned SA polyester polyol (A1), 1,4-BD / AA polyester polyol (A2) having an Mn of 8,000 or more, and 1,6-HD / AA polyester polyol (A3) having an Mn of 6,000 or more. The polyester polyol (B1) is a reaction product of dicarboxylic acids and diols, and is a bifunctional (hydroxyl number 2) polyol (diol). Preferably, the polyester polyol (B1) is obtained by polycondensation of dicarboxylic acids and diols.

[0056] As dicarboxylic acids used in polyester polyol (B1), for example, aliphatic dicarboxylic acids such as succinic acid, adipic acid, glutaric acid and azelaic acid; and aromatic dicarboxylic acids such as phthalic acid, isophthalic acid and terephthalic acid can be listed. As diols used in polyester polyol (B1), the same alcohols as those described in the description of SA polyester polyol (A1) can be listed.

[0057] Specific examples of the polyester polyol (B1) include polyethylene adipate diol, polybutylene adipate diol, polyhexylene adipate diol, polyneopentyl adipate diol, polyethylene / butylene adipate diol, polyneopentyl / hexylene adipate diol, poly-3-methylpentane adipate diol, and polybutylene isophthalate diol.

[0058] Among the polyester polyols (B1), 1,4-BD / AA polyester polyols (B1) having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid and having a number average molecular weight (Mn) of 1,000 to 5,000 are preferred. Among them, polybutylene adipate diol having an Mn of 1,200 to 4,000 is more preferred, and polybutylene adipate diol having an Mn of 1,500 to 3,000 is further preferred.

[0059] The polyether polyol (B2) is a difunctional (hydroxyl number 2) polyol (diol). The polyether polyol (B2) can be obtained, for example, by polymerizing or copolymerizing any one of an alkylene oxide (ethylene oxide, propylene oxide, and butylene oxide, etc.) and a heterocyclic ether (tetrahydrofuran, and 2-methyltetrahydrofuran, etc.). In addition, the polyether polyol (B2) can also be obtained by a dehydration condensation reaction of a diol such as 1,3-propylene glycol.

[0060] Examples of the polyether polyol (B2) include polyethylene glycol, polypropylene glycol, polyethylene glycol-polytetramethylene glycol (block or random), polytrimethylene ether glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol, etc. Among them, polyethylene glycol, polytrimethylene ether glycol, and polytetramethylene ether glycol are preferred from the viewpoint of flexibility.

[0061] In one embodiment of the moisture-curable urethane hot-melt resin composition, from the viewpoint of forming a more environmentally friendly composition, the polyol (B) (the polyester polyol (B1) and / or the polyether polyol (B2)) preferably contains a polyol (B1) made of a plant-derived raw material. b ). Polyols (B b ) can be called biomass polyol (B b As polyols using plant-derived raw materials (B b ), for example, polyester polyols (B b 1) and polyether polyol (B b 2); and polyether polyols (B b 2) etc. Examples of the plant-derived diols having 2 to 4 carbon atoms include plant-derived ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and 1,4-butylene glycol.

[0062] From the perspective that the above-mentioned effect of the polyol (B) can be easily expressed in a good balance with the effects of other polyols, the proportion of the polyol (B) in the polymer polyol component is preferably 10 to 98% by mass, more preferably 50 to 95% by mass, and even more preferably 60 to 90% by mass, based on the total amount of the polymer polyol component.

[0063] (Polycarbonate polyol (C))

[0064] The polymer polyol component preferably contains a polycarbonate polyol (C) in addition to the polyol (A) and the polyol (B). By using the polycarbonate polyol (C), a cured layer and a synthetic artificial leather having further improved hydrolysis resistance and abrasion resistance can be easily obtained.

[0065] Polycarbonate polyol (C) can be obtained by condensing diols such as 1,4-butanediol and 1,6-hexanediol with dialkyl carbonate while subjecting them to dealcoholization reaction. Polycarbonate polyol (C) is a bifunctional (hydroxyl number 2) polyol (diol), and crystalline or amorphous ones can be used as desired.

[0066] Examples of the polycarbonate polyol (C) include polytetramethylene carbonate diol, polypentamethylene carbonate diol, polyneopentyl carbonate diol, polyhexamethylene carbonate diol, poly(1,4-cyclohexanedimethylene carbonate) diol, and random / block copolymers thereof. Among them, polyhexamethylene carbonate diol (polycarbonate diol based on 1,6-hexanediol), poly(tetramethylene / decamethylene) carbonate diol (polycarbonate diol based on 1,4-butanediol and 1,10-decanediol), and poly(pentamethylene / hexamethylene) carbonate diol (carbonate diol based on 1,5-pentanediol and 1,6-hexanediol) are preferred.

[0067] In one embodiment of the moisture-curable urethane hot-melt resin composition, from the viewpoint of forming a more environmentally friendly composition, the polycarbonate polyol (C) preferably contains a polycarbonate polyol (C) using a plant-derived raw material. b ). Polycarbonate polyol (C b ) can be called biomass polycarbonate polyol (C b As a polycarbonate polyol (C b ), for example, polycarbonate polyols (C b ) etc. Examples of the plant-derived diols include plant-derived ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, and 1,10-decanediol.

[0068] From the perspective that the above-mentioned effect of the polycarbonate polyol (C) can be easily expressed in a well-balanced manner with the effects of the polyols (A) and (B), the proportion of the polycarbonate polyol (C) in the polymer polyol component is preferably 0 to 80% by mass, more preferably 4 to 40% by mass, and even more preferably 8 to 30% by mass, based on the total amount of the polymer polyol component.

[0069] When the polymer polyol component includes polycarbonate polyol (C), from the perspective of easily obtaining the target moisture-curable urethane hot-melt resin composition of the present disclosure, the total amount of polyol (B) and polycarbonate polyol (C) is preferably more than the amount of polyol (A). In addition, in this case, the ratio of the sum (total mass) of polyol (A), polyol (B) and polycarbonate polyol (C) relative to the total amount (total mass) of the polyol component is preferably 90% by mass or more. The sum of polyol (A), polyol (B) and polycarbonate polyol (C) can be the total amount of the polymer polyol component. Therefore, as described above, with respect to the ratio of the polymer polyol component in the polyol component, the ratio of the sum of polyol (A), polyol (B) and polycarbonate polyol (C) relative to the total amount of the polyol component is preferably 99.8% by mass or less, more preferably 99.5% by mass or less, and further preferably 99% by mass or less.

[0070] (Low molecular weight polyol component)

[0071] The low molecular weight polyol component used for the urethane prepolymer is preferably used in a smaller amount than the above-mentioned high molecular weight polyol component in the polyol component. Based on the total amount of the polyol component, the proportion of the low molecular weight polyol component in the polyol component is preferably 0.2 to 40% by mass, more preferably 0.5 to 20% by mass, and further preferably 1 to 10% by mass.

[0072] (Trifunctional polyol (D))

[0073] The low molecular weight polyol component used for the urethane prepolymer contains a trifunctional polyol (D) having three hydroxyl groups in one molecule and having a molecular weight (chemical formula weight) of 300 or less. The low molecular weight polyol component may contain other low molecular weight polyols (E) in addition to the trifunctional polyol (D) as needed.

[0074] Since the trifunctional polyol (D) has three hydroxyl groups in one molecule, it can be called a triol (D). By using this specific low-molecular trifunctional polyol (D), the target moisture-curable urethane hot-melt resin composition of the present disclosure can be obtained.

[0075] Examples of the trifunctional polyol (D) having a molecular weight of 300 or less include glycerol, trimethylolethane, trimethylolpropane, butanetriol, pentanetriol, hexanetriol, heptanetriol, and octantriol. Among them, glycerol and trimethylolpropane are preferred.

[0076] The amount of trifunctional polyol (D) used is calculated in relation to the above-mentioned polyol (A) in the following range. That is, the ratio of polyol (A) to trifunctional polyol (D) satisfies trifunctional polyol (D) (mmol) / polyol (A) (g) = 0.14 to 55 mmol / g. By making the trifunctional polyol (D) relative to the unit mass (1g) of polyol (A) 0.14 mmol or more and 55 mmol or less, the target moisture-curable urethane hot-melt resin composition of the present disclosure can be obtained. From the perspective of easily obtaining the target resin composition, trifunctional polyol (D) (mmol) / polyol (A) (g) is preferably 0.3 mmol / g or more, more preferably 0.5 mmol / g or more, and further preferably 1 mmol / g or more. In addition, trifunctional polyol (D) (mmol) / polyol (A) (g) is preferably 30 mmol / g or less, more preferably 20 mmol / g or less, and further preferably 10 mmol / g or more.

[0077] From the viewpoint that the above-mentioned effect of the trifunctional polyol (D) is easily exhibited, the proportion of the trifunctional polyol (D) in the low-molecular polyol component is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, and even more preferably 90 to 100% by mass, based on the total amount of the low-molecular polyol component.

[0078] As other low molecular weight polyols (E), for example, low molecular weight diols and tetrafunctional or higher low molecular weight polyols can be listed. As low molecular weight diols, for example, alcohols similar to the diols described in the description of SA polyester polyol (A1) can be listed. As tetrafunctional or higher low molecular weight polyols, for example, diglycerol, pentaerythritol, and dipentaerythritol can be listed.

[0079] 〔Polyisocyanate component〕

[0080] The polyisocyanate component used for the urethane prepolymer is not particularly limited, and a compound (polyisocyanate) having two or more isocyanate groups in one molecule can be used. As polyisocyanates, aromatic diisocyanates, alicyclic diisocyanates, aliphatic diisocyanates, and aliphatic diisocyanate modified bodies can be listed. Among them, aromatic diisocyanates, alicyclic diisocyanates, and aliphatic diisocyanate modified bodies are preferred, aromatic diisocyanates and aliphatic diisocyanate modified bodies are more preferred, and aromatic diisocyanates are further preferred.

[0081] Examples of the aromatic diisocyanate include 4,4'-diphenylmethane diisocyanate (MDI), 2,2'-MDI, 2,4'-MDI, 2,4-toluene diisocyanate (TDI), 2,6-TDI, meta-xylylene diisocyanate (XDI), 1,4-phenylene diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-isopropyl-1,3-phenylene diisocyanate, 4-butoxy-1,3-phenylene diisocyanate, 2,4-diisocyanate diphenyl ether, 1,5-naphthalene diisocyanate, and benzidine diisocyanate. Among these, MDI is preferred.

[0082] Examples of the alicyclic diisocyanate include 4,4′-methylenebis(cyclohexyl isocyanate), isophorone diisocyanate (IPDI), 1,3-bis(isocyanatomethyl)cyclohexane (hydrogenated XDI), dicyclohexylmethane-4,4′-diisocyanate (hydrogenated MDI), and 1-methylcyclohexane-2,4-diisocyanate (hydrogenated TDI).

[0083] Examples of the aliphatic diisocyanate include 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), and 1,10-decamethylene diisocyanate.

[0084] Examples of modified aliphatic diisocyanates include isocyanurates, allophanates, biuret forms, and adducts with polyols (such as trimethylolpropane) of aliphatic diisocyanates, etc. Among them, allophanates of aliphatic diisocyanates are preferred, and allophanates of HDI are more preferred.

[0085] [Method for producing urethane prepolymer]

[0086] The urethane prepolymer can be produced, for example, by a one-step method or a multi-step method by reacting a polyol component and a polyisocyanate component at preferably 60 to 150° C., more preferably 60 to 110° C., until the product reaches a theoretical NCO group content (mass %). When the polyol component and the polyisocyanate component react, a catalyst can be used in combination as needed. Examples of the catalyst include metal salts such as dibutyltin laurate, dioctyltin laurate, stannous octoate, lead octoate, tetra-n-butyl titanate, and organometallic derivatives; organic amines such as triethylamine; diazabicycloundecene-based catalysts, etc.

[0087] The polyol component and the polyisocyanate component are preferably reacted in the absence of a solvent such as an organic solvent, that is, in the absence of a solvent. By reacting the polyol component and the polyisocyanate component in the absence of a solvent such as an organic solvent, a solvent-free urethane prepolymer can be obtained.

[0088] It is preferred to use various polyols so that the amount of the polyol component used when manufacturing the urethane prepolymer falls within the range of the above-mentioned ratio of the polyol component. For example, with respect to the polymer polyol component, it is preferred that the polyol (A) and the polyol (B) and the polycarbonate polyol (C) used as needed are used in an amount within the range of the above-mentioned ratio in the polymer polyol component. In addition, with respect to the trifunctional polyol (D) used as the low-molecular polyol component, it is preferred to use it in an amount within the range of the ratio of the low-molecular polyol component in the above-mentioned polyol component. As a preferred example, the amount of the trifunctional polyol (D) used is preferably 0.5 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 0.5 to 10 parts by mass relative to 100 parts by mass of the total of the polyol (A), the polyol (B) and the polycarbonate polyol (C).

[0089] The moisture-curable urethane hot-melt resin composition can be mixed with various additives such as thermoplastic resin, tackifying resin, catalyst, pigment, antioxidant, ultraviolet absorber, surfactant, flame retardant, filler and foaming agent in appropriate amounts as needed. Among them, the moisture-curable urethane hot-melt resin composition can be substantially composed of the above-mentioned urethane prepolymer. Even when the resin composition is substantially composed of the urethane prepolymer, the composition can also contain components that are inevitably present due to the production of the urethane prepolymer.

[0090] As described above, in one embodiment, the moisture-curable urethane hot-melt resin composition has good stability over time in a molten state, and can form a cured layer having good initial adhesion, heat resistance, alcohol resistance, flexibility, hydrolysis resistance, and abrasion resistance. Therefore, the resin composition can be suitably used in applications such as synthetic leather that require heat resistance or high-temperature processing, and applications such as clothing that require washing resistance or abrasion resistance, and is expected to expand processability and applications.

[0091] In addition, by using the moisture-curable urethane hot-melt resin composition, a laminated body such as synthetic artificial leather having good cold-resistance bending, hydrolysis resistance, softness, wear resistance and heat resistance can be provided. For example, the resin composition can be used as a hot-melt adhesive for bonding a substrate layer such as a base cloth and a skin layer constituting the synthetic artificial leather. In addition, since the resin composition can form a cured layer having good initial adhesion and wear resistance, it can form a cured layer having the performance of maintaining good adhesion to a substrate layer such as a base cloth and having the performance of a skin layer such as a wear resistance.

[0092] <Laminated body>

[0093] The laminated body of one embodiment of the present invention comprises a substrate and a cured product layer of the moisture-curable urethane hot-melt resin composition disposed on the substrate. When the resin composition is used as a hot-melt adhesive, the substrate is used as one adherend and another substrate is used as another adherend, and they can be bonded. As substrates (adherends), in addition to the epidermis layer and substrate layer for synthetic leather described later, thin-film or sheet-like substrates such as optical films, optical plates, flexible printed circuit substrates, glass substrates, and substrates on which ITO is vapor-deposited, and substrates such as metals and non-metals (plastics, glass, etc.) can be cited.

[0094] The laminate can be preferably produced by applying a moisture-curable urethane hot-melt resin composition melted at 80 to 130° C. to a substrate and curing it with moisture to form a cured product layer. When the resin composition is used as a hot-melt adhesive, the molten resin composition is applied to one substrate, and then another substrate is attached thereto and moisture-cured.

[0095] The method for applying the moisture-curable urethane hot-melt resin composition to the substrate is not particularly limited, and a conventionally used method for applying hot-melt adhesives can be appropriately adopted. Examples of the coating method include comma coating, knife coating, roll coating, screen coating, T-die coating, fiber coating, gravure transfer coating engraved on a roll, and die coater method with a gear pump.

[0096] The laminate of this embodiment can also be configured as the synthetic artificial leather described later. In addition, as described above, the cured product layer of the moisture-curable urethane hot-melt resin composition used in the laminate has good initial adhesion and wear resistance, so it can form a skin layer directly bonded to a base material such as a base cloth constituting the synthetic artificial leather. Therefore, a synthetic artificial leather having a two-layer structure of a base material such as a base cloth and a skin layer composed of the cured product layer provided on the base material can be provided.

[0097] The synthetic leather with the cured product layer of moisture-curing urethane hot-melt resin composition as the epidermis layer can be manufactured as follows, for example. First, the moisture-curing urethane hot-melt resin composition forming the epidermis layer is melt-coated on release paper by the above-mentioned coating method, a base material such as a base cloth is pasted thereon, and the above-mentioned resin composition is cured by moisture to form a cured product layer (epidermis layer). Then, by peeling it off from the release paper, a synthetic leather with a 2-layer structure of a base material and an epidermis layer composed of a cured product layer arranged on the base material can be obtained. It should be noted that when pasting base materials such as base cloth, for example, a laminating machine equipped with a roller can be used for crimping. In addition, when the above-mentioned resin composition is cured by moisture, it can be ripened under specified temperature and humidity conditions.

[0098] <Synthetic leather>

[0099] A synthetic artificial leather according to one embodiment of the present invention comprises a base layer, a skin layer, and an adhesive layer provided between and bonding them together, wherein the adhesive layer is formed of a cured product layer of the moisture-curable urethane hot-melt resin composition.

[0100] Examples of the base fabric constituting the substrate layer include woven fabrics including twill and plain weave, raised fabrics obtained by mechanically raising the cotton grey fabric of the woven fabric, rayon fabric, nylon fabric, polyester fabric, Kevlar (registered trademark) fabric, nonwoven fabrics (polyester, nylon, various latexes), various films, sheets, etc. In addition, examples of the epidermis layer include those formed from epidermis layer forming coatings such as solution-type urethane resin compositions, water-based polyurethanes, and thermoplastic polyurethanes (TPU).

[0101] The synthetic artificial leather can be manufactured, for example, as follows. First, a coating for forming the epidermis layer is applied to release paper by a known method such as comma coating, blade coating, roller coating, gravure coating, die coating, spraying, etc. The applied coating is suitably dried to form the epidermis layer, and then the molten moisture-curable urethane hot-melt resin composition is applied to the epidermis layer by the above-mentioned coating method, and a base material layer such as a base cloth is pasted thereon and crimped using a laminator or the like. Then, as required, it is ripened under specified temperature and humidity conditions to form a cured product layer (adhesive layer). Next, by peeling it off from the release paper, the target synthetic artificial leather can be obtained.

[0102] A surface treatment agent can be applied to the surface of the epidermis layer (including the epidermis layer composed of the cured product layer described in the description of the above-mentioned laminate) constituting the synthetic leather. By using the surface treatment agent to treat the epidermis layer, a synthetic leather having a quality further suitable for commercialization can be obtained. The synthetic leather of this embodiment is suitable as a material constituting shoes, clothing, bags, furniture, vehicle interior materials (such as dashboards, doors, consoles, seats), etc.

[0103] It should be noted that, as described above, the following configurations may be adopted in one embodiment of the present invention.

[0104] [1] A moisture-curable urethane hot-melt resin composition comprising a reaction product of a polyol component and a polyisocyanate component, namely, a urethane prepolymer having an isocyanate group,

[0105] The polyol component comprises a high molecular weight polyol component and a low molecular weight polyol component.

[0106] The polymer polyol component comprises:

[0107] At least one polyol (A) selected from the group consisting of a polyester polyol (A1) having a structural unit derived from sebacic acid, a polyester polyol (A2) having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid and having a number average molecular weight of 8,000 or more, and a polyester polyol (A3) having a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid and having a number average molecular weight of 6,000 or more; and

[0108] at least one polyol (B) selected from the group consisting of polyester polyols (B1) other than the polyol (A) and polyether polyols (B2),

[0109] The low molecular weight polyol component includes a trifunctional polyol (D) having a molecular weight of 300 or less and having three hydroxyl groups in one molecule,

[0110] The ratio of the polyol (A) to the trifunctional polyol (D) satisfies the following: the trifunctional polyol (D) (mmol) / the polyol (A) (g) = 0.14 to 55 mmol / g.

[0111] [2] The moisture-curable urethane hot-melt resin composition according to [1] above, wherein the polyol (B) comprises a polyol (B) made of a plant-derived raw material. b ).

[0112] [3] The moisture-curable urethane hot-melt resin composition according to [1] or [2] above, wherein the polymer polyol component further comprises a polycarbonate polyol (C).

[0113] [4] The moisture-curable urethane hot-melt resin composition according to [3] above, wherein the polycarbonate polyol (C) comprises a polycarbonate polyol (C) made from a plant-derived raw material. b ).

[0114] [5] The moisture-curable urethane hot-melt resin composition according to [3] or [4] above, wherein the total amount of the polyol (B) and the polycarbonate polyol (C) is greater than the amount of the polyol (A),

[0115] The ratio of the total amount of the polyol (A), the polyol (B) and the polycarbonate polyol (C) to the total amount of the polyol components is 90% by mass or more.

[0116] [6] A laminate comprising: a substrate; and a cured product layer of the moisture-curable urethane hot-melt resin composition according to any one of [1] to [5] above, provided on the substrate.

[0117] [7] A synthetic artificial leather comprising a base layer, a skin layer, and an adhesive layer disposed between and bonding them together, wherein the adhesive layer is a cured product layer of the moisture-curable urethane hot-melt resin composition described in any one of [1] to [5] above.

[0118] Example

[0119] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples.

[0120] <Materials>

[0121] The polymer polyol materials used are shown in Table 1 below.

[0122] Table 1

[0123]

[0124] <Production of moisture-curable urethane hot-melt resin composition>

[0125] (Example 1)

[0126] A polyol component and a polyisocyanate component were added and mixed in a glass reaction vessel equipped with a stirrer, a thermometer and a gas inlet, and the reaction vessel was heated and decompressed to perform a dehydration treatment, and nitrogen was further sealed, and the reaction was stirred for 120 minutes while the internal temperature was 100° C. The polyol component used a high molecular weight polyol component (total 100 parts by mass) containing 10 parts by mass of polyester polyol (A1), 45 parts by mass of polyester polyol (B1-1) and 45 parts by mass of polyether polyol (B2-1), and 0.5 parts by mass of trimethylolpropane of a trifunctional polyol (D) component having a molecular weight of 300 or less. The ratio of polyol (A) to trifunctional polyol (D) was set to trifunctional polyol (D) (mmol) / polyol (A) (g) = 0.37 mmol / g. The polyisocyanate component used 22.35 parts by mass of 4,4′-diphenylmethane diisocyanate (MDI), and the molar ratio of NCO groups of MDI to OH groups of the polyol component (NCO groups / OH groups) was set to 1.7. In this way, the urethane prepolymer of Example 1 was obtained.

[0127] (Examples 2 to 17 and Comparative Examples 1 to 10)

[0128] The urethane prepolymers of each example were obtained in the same manner as in Example 1 except that the type and amount of the polyol component and the amount of the polyisocyanate component (MDI) were changed as shown in the upper part of the following Table 2 (Tables 2-1 to 2-6). The values ​​of "trifunctional polyol (D) / polyol (A) [mmol / g]" and "NCO group / OH group (molar ratio)" are shown together in the middle part of Table 2 along with the changes in the amounts of the polyol component and the polyisocyanate component. It should be noted that, in Comparative Example 10 in which trifunctional polyol (D) (mmol) / polyol (A) (g) = 56.0 mmol / g, gelation occurred during the stirring reaction, and the evaluation described below could not be performed.

[0129] <Evaluation>

[0130] As the moisture-curable urethane hot-melt resin composition of each example (hereinafter sometimes referred to as "hot-melt resin composition"), the urethane prepolymer obtained in each example was subjected to the following evaluations. In the evaluation criteria of each item, AA, A, and B are acceptable good levels, and C is an unacceptable level. The evaluation results are shown in the lower part of Table 2.

[0131] (Temperature stability in molten state)

[0132] The hot-melt resin composition of each example was heated to 100°C and melted, and the change in viscosity over time and the visual confirmation of the precipitate were carried out under the conditions of 100°C and 24 hours. The viscosity of the hot-melt resin composition was measured using a BM type viscometer (Tokyo Instrument Manufacturing Co., Ltd.) under the conditions of rotor No. 4, 30 rpm and 100°C. Based on the above-mentioned change in viscosity over time (viscosity change rate) and the presence or absence of precipitates, the temporal stability of the hot-melt resin composition in the molten state was evaluated according to the following evaluation criteria. The viscosity change rate is calculated by viscosity change rate (%) = {(viscosity after 24 hours at 100°C - initial viscosity at 100°C) / initial viscosity at 100°C} × 100.

[0133] AA: No sediment, viscosity change rate is less than 20%.

[0134] A: There is no sediment, and the viscosity change rate is 20% or more and less than 50%.

[0135] B: There is sediment and the viscosity change rate is less than 100%.

[0136] C: There is a precipitate, and the viscosity change rate is 100% or more.

[0137] (Preparation of evaluation film)

[0138] The hot melt resin composition of each example was melted at 100°C and applied onto release paper in such a manner that the film thickness after application was 50 to 70 μm. Then, the film was aged for 72 hours at a temperature of 25°C and a relative humidity of 60% (60% RH), and further stored at room temperature (20°C) for 1 day to obtain a film for evaluation with release paper.

[0139] (Thermal Softening Point)

[0140] The thermal softening point was measured using an evaluation film (1.5 cm wide and 6 cm long) obtained by peeling off the release paper from the evaluation film with release paper. Figure 1 As shown in the figure, the jigs 12 are installed above and below the evaluation film 10, and the jigs 12 are further fixed using CELLOTAPE (registered trademark). When the film is hung on one of the jigs 12, a pressure of 450 g / cm is applied. 2 The weight 14 with a load of 100 was used to prepare the sample 16. It should be noted that the central portion of the evaluation film 10 with a length of 2 cm was not covered by CELLOTAPE (registered trademark). Figure 2 As shown, the fixture 12 of the sample 16 without the weight 14 installed is installed on the rotating disk 22 of the gear oven 20. Then, the rotating disk 22 is rotated at 5 rpm, and the temperature in the gear oven 20 is raised from room temperature at a rate of 3°C / minute. The temperature (°C) when the evaluation film 10 is broken or stretched to twice is taken as the thermal softening point. According to the value of its thermal softening point (°C), the heat resistance based on the thermal softening point is evaluated according to the following evaluation criteria. The higher the thermal softening point, the higher the heat resistance of the film.

[0141] A: The thermal softening point is 185°C or higher.

[0142] B: The thermal softening point is 170°C or higher and lower than 185°C.

[0143] C: Thermal softening point is less than 170°C.

[0144] (Alcohol resistance)

[0145] The evaluation film obtained by peeling off the release paper from the evaluation film with release paper was cut into 50 mm × 50 mm and immersed in ethanol at 25°C placed in a petri dish for 10 minutes. After 10 minutes, the evaluation film was taken out from the ethanol, the state of the evaluation film was confirmed by visual inspection, and the alcohol resistance was evaluated according to the following evaluation criteria. The following linear swelling rate is calculated by linear swelling rate (%) = (length of one side of the evaluation film after immersion (mm) / length of one side of the evaluation film before immersion (50 mm)) × 100.

[0146] AA: The linear swelling ratio of one side of the evaluation film was less than 120%.

[0147] A: The linear swelling ratio of one side of the evaluation film is 120% or more and less than 150%.

[0148] B: The linear swelling ratio of one side of the evaluation film is 150% or more.

[0149] C: The evaluation film was dissolved.

[0150] (Initial Adhesion)

[0151] The hot-melt resin composition of each example was heated to 100°C to melt it, and was evenly coated on a PET film (3 cm wide) with a coating amount of 100 μm / wet to form a coating layer of the hot-melt resin composition. After coating, the base fabric (fabric) was immediately crimped using a laminator, wherein the laminator was set to a roller temperature of 30°C and a lamination gap of 70% relative to the total thickness of the base fabric, the coating layer and the PET film. After lamination for 10 minutes, the bonding strength was measured using a digital dynamometer (manufactured by Nidec Shinpo Co., Ltd.), and the initial bonding was evaluated according to the following evaluation criteria. It should be noted that when the bonding strength after lamination for 10 minutes is less than 0.2 kg / 3 cm, then in the subsequent processing steps, the base fabric and the resin layer formed by the hot-melt resin composition will be peeled off or twisted again, and the risk of defectiveness will increase. According to this view, the bonding strength after lamination for 10 minutes is 0.2 kg / 3 cm or more as qualified.

[0152] A: The bonding strength is 0.4kg / 3cm or more.

[0153] B: The adhesive strength is 0.2 kg / 3 cm or more and less than 0.4 kg / 3 cm.

[0154] C: The bonding strength is less than 0.2kg / 3cm.

[0155] <Production of synthetic leather for evaluation>

[0156] (1) Preparation of epidermis

[0157] The epidermis layer in the synthetic artificial leather is prepared as described below. First, 100 parts by mass of a solution-type urethane resin (trade name "RESAMINE NE-8875-30M", manufactured by Dainichi Seika Industries Co., Ltd.), 10 parts by mass of a colorant (trade name "Seika Seven BS-780 (S) Black", manufactured by Dainichi Seika Industries Co., Ltd.), 25 parts by mass of methyl ethyl ketone (MEK) as a diluent, and 25 parts by mass of dimethylformamide (DMF) are mixed to prepare a urethane resin composition for the epidermis layer. Next, a rod coater is used to evenly apply the prepared urethane resin composition to a release paper at a coating amount of 250 μm / wet. Then, it is dried at 120°C for 5 minutes to obtain an epidermis layer with a film thickness of 30 to 50 μm formed on the release paper.

[0158] (2) Preparation of standard synthetic leather for softness evaluation

[0159] Using the epidermis layer and adhesive obtained in the above-mentioned "(1) Preparation of epidermis layer", a standard synthetic artificial leather for softness evaluation is prepared as follows. First, 100 parts by mass of a solution-type urethane resin (trade name "RESAMINE UD-8373BL", manufactured by Dainichi Seika Industries Co., Ltd.), 12 parts by mass of an isocyanate crosslinking agent (trade name "RESAMINE NE", manufactured by Dainichi Seika Industries Co., Ltd.), and 30 parts by mass of methyl ethyl ketone (MEK) and 30 parts by mass of dimethylformamide (DMF) as diluents are mixed to prepare an adhesive. Next, the prepared adhesive is applied to the epidermis layer on the release paper obtained in the above-mentioned "(1) Preparation of epidermis layer" in a manner to form a dry film thickness of about 100 μm, thereby forming a coating layer of the adhesive. After removing the solvent in the adhesive coating layer by heating, the base fabric (woven fabric) was immediately pressed using a laminator, wherein the laminator was set to a roll temperature of 40°C and a lamination gap of 70% relative to the total thickness of the base fabric, coating layer (adhesive layer), skin layer and release paper. Then, the coating layer was cured at 50°C for 48 hours to form an adhesive layer, and then the release paper in contact with the skin layer was peeled off to obtain a standard synthetic artificial leather.

[0160] (3) Preparation of synthetic leather in each example

[0161] Using the epidermis layer obtained in the above "(1) Preparation of epidermis layer" and the hot-melt resin composition of each example, the synthetic artificial leather of each example is prepared as follows. First, the hot-melt resin composition is heated to 100°C to melt it, and the molten hot-melt resin composition is applied to the epidermis layer on the release paper obtained in the above "(1) Preparation of epidermis layer" in a manner to form a dry film thickness of about 100 μm, thereby forming a coating layer of the hot-melt resin composition. After coating, the base fabric (woven fabric) is immediately crimped using a laminator, wherein the laminator is set to a roller temperature of 30°C and a lamination gap of 70% relative to the total thickness of the base fabric, the coating layer (hot-melt resin composition layer), the epidermis layer and the release paper. Then, it is aged at 25°C and 60% RH for 48 hours to form a cured layer of the hot-melt resin composition, and then the release paper in contact with the epidermis layer is peeled off. In this way, a synthetic artificial leather is obtained in which a base fabric (woven fabric) as a substrate layer and a skin layer are bonded to each other via a cured product layer of a hot-melt resin composition as an adhesive layer.

[0162] (Cold resistance and bending)

[0163] For each example of synthetic leather, a test piece with a width of 50 mm and a length of 150 mm (evaluation range of 100 mm) was prepared. Using the prepared test piece, a bending test was performed using a Demethia Flexing Tester (model "No.119-L Demethia Flexing Tester", manufactured by Yasuda Seiki Seisakusho Co., Ltd.) in an environment of -10°C, in a range of 72 to 108% of telescopic bending, and at a low temperature of -10°C. In addition, the cold resistance bending property was evaluated according to the following evaluation criteria.

[0164] AA: No cracks after 60,000 times.

[0165] A: No cracks after 30,000 times, but cracks before 60,000 times.

[0166] B: No cracks after 10,000 times, but cracks before 30,000 times.

[0167] C: Cracks after 10,000 cycles.

[0168] (Hydrolysis resistance)

[0169] For each example of synthetic leather, the bonding strength before and after the hydrolysis resistance test was measured, and the hydrolysis resistance was evaluated by comparing them. Specifically, a hot melt tape was pressed onto the upper surface of the skin layer of the synthetic leather for 1 minute using an iron at 140°C, and cooled at room temperature (20°C) for 1 hour, and then the base fabric in the synthetic leather and the skin layer in close contact with the hot melt tape were peeled off in a 180° direction at a peeling speed of 200 mm / min, and the strength was measured using a tensile tester (model "Autograph AGS-100A", manufactured by Shimadzu Corporation) as the bonding strength.

[0170] On the other hand, the synthetic leather of each example was placed in a constant temperature chamber at 70°C and 95% RH for a predetermined time, and then the adhesive strength after the hydrolysis resistance test was measured in the same manner as above. The adhesive strength before the test was compared with the adhesive strength after the test, and the hydrolysis resistance was evaluated according to the following evaluation criteria. It should be noted that the retention rate of adhesive strength refers to the ratio of the adhesive strength after being placed in the chamber for a predetermined time to the adhesive strength before being placed in the chamber.

[0171] AA: The retention rate of the adhesive strength after storage for 8 weeks is 70% or more.

[0172] A: The retention rate of the adhesive strength after storage for 5 weeks is 70% or more.

[0173] B: The retention rate of the adhesive strength after storage for 5 weeks is 50% or more and less than 70%.

[0174] C: The retention rate of the adhesive strength after storage for 5 weeks is less than 50%.

[0175] (Softness)

[0176] Each synthetic artificial leather was compared with the standard synthetic artificial leather obtained in the above "(2) Preparation of standard synthetic artificial leather for softness evaluation" by touch, and softness was evaluated according to the following evaluation criteria based on the standard synthetic artificial leather.

[0177] AA: Noticeably softer than standard synthetic leatherette.

[0178] A: Softer than standard synthetic leather.

[0179] B: As soft as standard synthetic leather.

[0180] C: Noticeably harder than standard synthetic leather.

[0181] (Abrasion resistance)

[0182] The hot-melt resin composition of each example is heated to 100°C to melt it, and the molten hot-melt resin composition is applied to the release paper in a manner of forming a dry film thickness of about 100 μm to form a coating layer of the hot-melt resin composition. After coating, the base fabric (woven fabric) is immediately crimped using a laminator, wherein the laminator is set to a roller temperature of 30°C and a lamination gap of 70% relative to the total thickness of the base fabric, the coating layer (hot-melt resin composition layer) and the release paper. Then, it is aged for 48 hours at 25°C and 60%RH to form a cured layer of the hot-melt resin composition, and then the release paper in contact with the cured layer is peeled off. In this way, a laminated body having a base fabric (woven fabric) and a skin layer composed of a cured layer of the hot-melt resin composition arranged on the base fabric is prepared as a two-layer structure. It is used as a synthetic leather for the wear resistance test described below.

[0183] For each synthetic leather used in the wear resistance test, a circular test piece with a diameter of 11.5 cm was prepared. The test piece and Taber abrasion tester (manufactured by Yasuda Seiki Seisakusho Co., Ltd.) were used to perform the wear resistance test under the conditions of a load of 500 g, a rotation speed of 60 ± 2 rpm, and a wear wheel of CS-10. The wear resistance was evaluated according to the following evaluation criteria.

[0184] AA: No scratches or other appearance changes after 1500 times.

[0185] A: There are no scratches or other appearance changes after 1000 times, but there are scratches or other appearance changes before 1500 times.

[0186] B: No scratches or other appearance changes after 500 times, but scratches or other appearance changes before 1000 times.

[0187] C: Less than 500 times with scratches and other appearance changes

[0188] <Heat resistance (heat creep test)>

[0189] The creep test is a test in which a constant load is applied to a test piece for a long period of time at a high temperature and the amount of deformation and the time until fracture are measured. Specifically, 1) to 8) are performed as follows.

[0190] 1) The hot-melt resin composition and coating bar of each example to be tested were placed in an oven at 100° C. and preheated.

[0191] 2) A hot-melt resin composition was applied to the polyurethane (PU) resin layer of the wet film-forming cloth (A) at a 200 μGap (thickness 200 μm), and immediately bonded to the PU resin layer of the wet film-forming cloth (B).

[0192] It should be noted that as the wet film-forming cloth (A) and the wet film-forming cloth (B), the following synthetic artificial leather is used, in which a polyurethane resin solution (trade name "RESAMINE CU-4340NS" (resin solid content 30% by mass, manufactured by Dainichi Seika Industries) diluted with DMF to a solution with a solid content of 15% by mass) is applied to a non-woven fabric used as a substrate, and the solution is coagulated and de-DMFed in a water tank and then dried to form a PU resin layer, and a porous layer with a thickness of 800 to 1000 μm after drying is formed on the substrate.

[0193] 3) After curing the laminated product at 25°C / 60%RH for 24 hours, the heat resistance was measured according to the following procedure.

[0194] 4) The oven was set to 170° C. Also, the bonded product was cut into pieces having a width of 3 cm and a length of 12 cm or more to prepare test pieces.

[0195] 5) The edges of the test piece were peeled off from the bonding surface, and clamps were installed and fixed on the wet film-forming cloth (A) side and the wet film-forming cloth (B) side, and a 3 kg weight was hung on one side.

[0196] 6) Hang the test specimen into an oven at 170°C and quickly close the oven door.

[0197] 7) Close the door and leave it for 5 minutes.

[0198] 8) After 5 minutes, the test piece was taken out immediately, and the peeling length and peeling state after standing at 170°C for 5 minutes were observed. The heat resistance was evaluated according to the following evaluation criteria.

[0199] A: The peeling length is less than 2 cm, and the peeling state is that the substrate is broken.

[0200] B: The peeling length is 2 cm or more and less than 5 cm, and the peeling state is that the substrate is broken.

[0201] C: The peeling length is 5 cm or more or the peeling state is PU resin surface peeling.

[0202] Table 2

[0203]

[0204] Table 22

[0205]

[0206] Table 2-3

[0207]

[0208] Table 2-4

[0209]

[0210] Table 25

[0211]

[0212] Table 26

[0213]

[0214] Description of Reference Numerals

[0215] 10 Evaluation film

[0216] 12. Fixture

[0217] 14 Weights

[0218] 16 Samples

[0219] 20 Gear Oven

[0220] 22 Rotating disk

Claims

1. A moisture-curable urethane hot-melt resin composition comprising a reaction product of a polyol component and a polyisocyanate component, namely, a urethane prepolymer having an isocyanate group, The polyol component comprises a high molecular weight polyol component and a low molecular weight polyol component. The polymer polyol component comprises: At least one polyol (A) selected from the group consisting of a polyester polyol (A1) having a structural unit derived from sebacic acid, a polyester polyol (A2) having a structural unit derived from 1,4-butanediol and a structural unit derived from adipic acid and having a number average molecular weight of 8,000 or more, and a polyester polyol (A3) having a structural unit derived from 1,6-hexanediol and a structural unit derived from adipic acid and having a number average molecular weight of 6,000 or more; and at least one polyol (B) selected from the group consisting of polyester polyols (B1) other than the polyol (A) and polyether polyols (B2), The low molecular weight polyol component includes a trifunctional polyol (D) having a molecular weight of 300 or less and having three hydroxyl groups in one molecule, The ratio of the polyol (A) to the trifunctional polyol (D) satisfies the following: the trifunctional polyol (D) (mmol) / the polyol (A) (g) = 0.14 to 55 mmol / g.

2. The moisture-curable urethane hot-melt resin composition according to claim 1, wherein The polyol (B) includes a polyol (B) using a plant-derived raw material. b ).

3. The moisture-curable urethane hot-melt resin composition according to claim 1, wherein The polymer polyol component further includes a polycarbonate polyol (C).

4. The moisture-curable urethane hot-melt resin composition according to claim 3, wherein The polycarbonate polyol (C) includes a polycarbonate polyol (C) using a plant-derived raw material. b ).

5. The moisture-curable urethane hot-melt resin composition according to claim 3, wherein The total amount of the polyol (B) and the polycarbonate polyol (C) is greater than the amount of the polyol (A), The ratio of the total amount of the polyol (A), the polyol (B) and the polycarbonate polyol (C) to the total amount of the polyol components is 90% by mass or more.

6. A laminate comprising: Base material, and A cured product layer of the moisture-curable urethane hot-melt resin composition according to any one of claims 1 to 5 provided on the substrate.

7. A synthetic artificial leather comprising a base layer, a surface layer, and an adhesive layer disposed between and bonding them together, The adhesive layer is a cured product layer of the moisture-curable urethane hot-melt resin composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Moisture-curable polyurethane hot melt resin composition

    CN111741992A

  • Polyurethane prepolymer, adhesive and synthetic imitation leather

    CN111902443A

  • Light / moisture-curable urethane-based compound, light / moisture-curable urethane polymer, and light / moisture-curable resin composition

    CN113242869A

  • Moisture-curable polyurethane hot melt resin composition

    CN114144444A

  • Moisture-hardening urethane sealant composition

    JP1996157801A

Cited By

  • Surface protective film, optical member, and electronic member

    CN120173544A